Diethylamine Dess-Martin periodinane: an efficient catalyst-oxidant combination in a sequential, one-pot synthesis of difficult to access 2-amino-3,5-dicarbonitrile-6-sulfanylpyridines at ambient temperature - Kupwade, Ravindra V.; Khot, Supriya; Kulkarni, M. A.; Desai, Uday V.; Wadgaonkar, Prakash P. (RSC Advances, 2017)
Herein, diethylamine Dess–Martin periodinane has been demonstrated for the first time as an efficient catalyst–oxidant combination in a sequential, one-pot synthesis of medicinally privileged but difficult to access 2-amino-3,5-dicarbonitrile-6-sulfanylpyridines via a pseudo-four component reaction between 2,6-disubstituted benzaldehydes, malononitrile, and thiols. Ambient reaction conditions, excellent yields, and total avoidance of conventional isolation as well as purification are the noteworthy merits of this developed protocol.